A Secure Cloud Service Game Theory Approach to Demand Response Modelling for Residential Users in Smart Grid - L, Priya; V, Gomathi; Palanichamy, Naveen (JOIV : International Journal on Informatics Visualization, 2025)
In today's world, electricity has become the keystone for every activity undertaken. As the population increases, the electricity demand has reached unprecedented levels, putting strain on electrical grids. In many developing countries, the residential sector consumes 60% of the peak load. The negative consequences of this trend provide a pathway for frequent brownouts, which lead to enormous losses for industries as well as residential households. To date, the flexibility of energy is usually achieved on the generation side. However, an easier way to counter this would be to manage usage on the demand side. The development of smart grid facilities has enabled communication between utilities and consumers. Therefore, the demand response functionality shows greater potential to stabilize the power supply and demand for the utility and consumers, respectively. In this paper, an intelligent secure cloud service game theory-based demand response modelling algorithm is proposed to handle peak demand in the residential sector. This innovative strategy enables residential consumers to achieve mutually beneficial outcomes. Enhancing communication security between utility providers and consumers, optimizing renewable energy utilization, and improving cost-effectiveness and reliability in electricity production and delivery are vital for meeting the rising demand. The simulation results suggest that the proposed approach efficiently reduces the Peak-to-Average Ratio, leading to mutual advantages for both consumers and utility providers. This approach addresses the growing demand for electricity while promoting sustainable energy through improved energy management practices.